Developing an ontology for a graph database in agriculture: Technical guidelines - Laporte, Marie-Angélique; Idicula, Siju; Davoglio Tolotti, Rafael; Burra, Dharani Dhar; Quirós, Carlos F.; Arnaud, Elizabeth (2022)
These guidelines are aimed at users already familiar with an Ontology structure, and its definitions of classes, properties and axioms. This document guides the reader through the steps of an ontology modeling process to be integrated into a multi-source graph database such as NEO4J . The development of a Soil Ontology is used as an example. It covers the principles of modeling to include soil measurements, geocoordinates and units, so that the ontology can support data transformation and queries. These guidelines result from collaboration between the Varda platform development team and the CGIAR Ontology Team.